Stressed out on four continents: time crunch or yuppie kvetch? - Daniel S. Hamermesh; Jungmin Lee (Institute for the Study of Labor (IZA), 2005)
Social commentators have pointed to problems of workers who face time stress an absence of sufficient time to accomplish all their tasks. An economic theory views time stress as reflecting how tightly the time constraint binds households. Time stress will be more prevalent in households with higher full earnings and whose members work longer in the market or on required homework. Evidence from Australia (2001), Germany (2002), the United States (2003) and Korea (1999) corroborates the theory. Adults in households with higher earnings perceive more time stress for the same amount of time spent in market work and household work. The importance of higher full earnings in generating time stress is not small, particularly in U.S. much is yuppie kvetch.
Keywords: J22; 330; time stress; household production; feeling rushed; Stress; Zeitbudgetforschung; Zeitallokation; Geschlecht; Industriestaaten